Regression Factors of Small Businesses Performance: Conceptual Model - Yusra Yaseen , Lazim; Noor Azlinna, Azizan; Sorooshian, Shahryar (Penerbit Universiti Malaysia Pahang, 2015)
This study represents an attempt to develop a model that demonstrates the relationship between HRM Practices, Governmental Support and Organizational performance of small businesses. Furthermore, this study assay to unfold the socalled “Black Box” to clarify the ambiguous relationship between HRM practices and organizational performance by considering the pathway of logical sequence influence. The model of this study consists two parts, the first part devoted to examining the causal relationships among HRM practices, employees’ outcomes, and organizational performance. The second part assesses the direct relationship between the governmental support and organizational performance. It is hypothesized that HRM practices positively influence organizational performance, and that employees’ outcomes mediating the relationship between HRM and organizational performance. Also, it is hypothesized that the governmental support impact positively organizational performance. The expected results of this study demonstrate that employee outcomes partially mediating the relationship between HRM practices and organizational performance. And governmental support fully impact organizational performance.